Group portrait of the 1957 Methodist Youth Institute Worship and Fine Arts meeting at Monte Toyon - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the Methodist Youth Institute Worship and Fine Arts meeting, held August 17-24, 1957 at Monte Toyon in Aptos, California.